2022
DOI: 10.3390/polym14153176
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume and Permeability of Mixed Matrix Membranes Made from a Terbutil-M-terphenyl Polyamide and a Porous Polymer Network

Abstract: A set of thermally rearranged mixed matrix membranes (TR-MMMs) was manufactured and tested for gas separation. These membranes were obtained through the thermal treatment of a precursor MMM with a microporous polymer network and an o-hydroxypolyamide,(HPA) created through a reaction of 2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane (APAF) and 5′-terbutil-m-terfenilo-3,3″-dicarboxylic acid dichloride (tBTmCl). This HPA was blended with different percentages of a porous polymer network (PPN) filler, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The gas permeability of MMMs and the corresponding neat polymeric matrices of HPA and PAA are shown as a function of the kinetic diameter of the permeated gases, as given by Breck (1975) [ 40 ] for different filler contents, both before and after thermal rearrangement (represented in Figure 9 ). Recently, Soto et al (2022) [ 25 , 41 ] proposed and validated a correlation between permeability and free volume, as: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas permeability of MMMs and the corresponding neat polymeric matrices of HPA and PAA are shown as a function of the kinetic diameter of the permeated gases, as given by Breck (1975) [ 40 ] for different filler contents, both before and after thermal rearrangement (represented in Figure 9 ). Recently, Soto et al (2022) [ 25 , 41 ] proposed and validated a correlation between permeability and free volume, as: …”
Section: Resultsmentioning
confidence: 99%
“…The acronyms of the manufactured membranes are shown in Table 1 . Note that we only included up to 30% PPN content, because previous experience revealed that PPN content over 30% strongly decreases the selectivity and worsens the mechanical properties [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The van der Waals volume can be evaluated by using the Bondi's group contribution theory [11] or by molecular modeling of the polymer repeating units, with programs like Hyperchem Molecular Modeling (Hypercube, Gainesville, FL, USA) [20,21] or DS BIOVIA Materials Studio software (2023 v23.1.0.3829) (BioVia Dassault Systémes, San Diego, CA, USA) [8,22].…”
Section: Free Volume Fractionmentioning
confidence: 99%
“…We have recently proposed and tested a quantitative correlation of free volume fraction with permeability [ 7 , 8 , 9 , 10 ] that we want to verify here for a homologous series of rather similar polyimides with a wide range of permeabilities. We will test as well whether that quantitative correlation can be applied to d-spacing too.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique by itself is not decisive since in many cases, it is difficult to quantify these morphologies in enough detail. The determination of the fractional free volume (FFV) or the density of the MMMs compared to their constituents also informs us about free spaces or the penetration of the polymer into the filler matrix [26,27]. On the other hand, the rigidification of the polymer chains at the interfaces can be studied by analyzing properties such as the glass transition temperature (Tg) or the most probable intersegmental distance as a function of the filler content [14].…”
Section: Introductionmentioning
confidence: 99%